The Yin and Yang of R-loop biology. (June 2015) - Costantino, Lorenzo; Koshland, Douglas
Abstract : RNA performs diverse functions in cells, directing translation, modulating transcription and catalyzing enzymatic reactions. Remarkably RNA can also anneal to its genomic template co- or post-transcriptionally to generate an RNA–DNA hybrid and a displaced single-stranded DNA. These unusual nucleic acid structures are called R-loops. Studies in the last decades concentrated on the detrimental effects of R-loop formation, particularly on genome stability. In fact, R-loops are thought to play a role in several human diseases like cancer and neurodegenerative syndromes. But recent data has revealed that R-loops can also have a positive impact on cell processes, like regulating gene expression, chromosome structure and DNA repair. Here we summarize our current understanding of the formation and dissolution of R-loops, and discuss their negative and positive impact on genome structure and function.